SAT0578 Patients with Rheumatoid Arthritis, Spondyloarthritis and Psoriatic Arthritis Treated with BIOLOGICS Use Similar Coping Strategies: A Study of 671 Patients. (10th June 2014) - Rat, A.-C.; Fautrel, B.; Flipon, E.; Gossec, L.; Marguerie, L.; Nataf, H.; Pallot Prades, B.; Poilvert, R.M.; Royant, V.; Sadji, F.; Sordet, C.; Thevenot, C.; et al.
Abstract : Background: Several coping models have been proposed to understand the psychological adjustment to Rheumatoid Arthritis (RA). Coping strategies of other inflammatory arthritis (IA) have been less extensively studied and have not been compared to each other. Moreover, biologics could dramatically influence coping strategies. Objectives: To describe and compare the coping strategies of 3 groups of patients with IA treated by biologics: RA, Axial Spondyloarthritis (AS) and Psoriatic arthritis (PsA). Methods: Data were obtained from a national cross-sectional survey aimed at studying self-care skills of patients treated by biologics for IA. To be as representative as possible of the patients treated by biologics, rheumatologists were randomly sampled from the national directory. They were invited to include 3 consecutive patients. All patients completed sociodemographic and clinical data, quality of life (SF12) and coping style (Brief Cope) self-administered questionnaires. The Brief Cope, a 28-item questionnaire determines the frequency with which people engage in 14 different coping mechanisms (self-distraction, active coping, denial, substance use, using emotional support, behavioural disengagement, religion, acceptance, venting, using instrumental support, positive reframing, self-blame, planning, humour). Scores on each subscale range from 2 to 8. The 3 IA were compared with analyses of variance. Results: Of the 671 patients included, 67% were women, 61% had RA, 31% AS and 9% PsA, 63% were treated by subcutaneous antiTNF, 20% by non antiTNF biologics. The mean age was 53±13 years old, the SF12 physical and mental component summaries were 43.2±8.8, and 47.4±7.1 respectively. The coping strategies the most frequently used (median >5) were acceptance, active coping, self-distraction, positive reframing and planning. Among the 14 coping mechanisms, only 4 were different (Table). PsA patients used more humour and less behavioural disengagement strategies. RA patients used more religion strategy and AS used less acceptance strategy. Scores were not associated with age (r <0.15); humour was more frequently used by men and religion by women. After adjustment on sex, religion and humour dimensions were no more different between IA. Conclusions: The differences of coping strategies between RA, AS and PsA patients treated by biologics are negligible. Biologics probably reduce these differences. These results help physicians to better understand coping strategies of patients with IA to better care for them in their adaptation to their chronic disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4178